STRATEGI INTEGRATED MARKETING COMMUNICATION PARIWISATA BERBASIS BUDAYA MELALUI KESENIAN KRIDO BUDOYO DI DESA NJRAKAH SELO BOYOLALI - Dwi Kristiani; Nuning Lisdiana (EKOBIS, 2019)
Jrakah Village is one of the villages in Selo District, Boyolali Regency, besides having natural attractions, namely the beautiful mountain scenery; it also has cultural tourism in the form of dances which are incorporated in the Krido Budoyo art gallery. This art has its own attraction to attract local and foreign tourists. The tourism program will be successful if the promotion strategy is implemented appropriately. The purpose of this study is to describe Integrated Marketing Communication and to find out the elements of promotion that are applied to cultural tourism in Jrakah Selo Village. In addition, it is also to find out the obstacles faced by the Department of Tourism in promoting cultural tourism in the village of Jrakah Selo. This type of research is descriptive research. The result of his research is that the Integrated Marketing Communication run by the Krido Budoyo Arts group has not been maximized because it has only used a number of social media, other aspects such as a convenient venue are also not yet available. is the absence of synergy between the roles of government, art groups, tourism businesses and local communities who are members of MSE. There needs to be a joint commitment in marketing the Krido Budoyo art and partnerships with third parties in developing and marketing Krido Budoyo art